Coarse-graining amorphous plasticity: impact of rejuvenation and disorder - Tyukodi, Botond; Barbot, Armand; García-García, Reinaldo; Lerbinger, Matthias; Patinet, Sylvain; Vandembroucq, Damien (Comptes Rendus. Physique)
The coarse-graining of amorphous plasticity from the atomistic to the mesoscopic scale is studied in the framework of a simple scalar elasto-plastic model. Building on recent results obtained on the atomistic scale, we discuss the interest of a disordered landscape-informed threshold disorder to reproduce the physics of amorphous plasticity. We develop a rejuvenation scenario that reproduces quasi-quantitatively the evolution of the mean local yield stress and the localization behavior. We emphasize the crucial role of two dimensionless parameters: the relative strength of the yield stress disorder with respect to the typical stress drops associated with a plastic rearrangement, and the age parameter characterizing the relative stability of the initial glass with respect to the rejuvenated glass that emerges upon shear deformation.